Cost‐effectiveness of trans‐nasal endoscopic sphenopalatine artery ligation vs arterial embolisation for intractable epistaxis: Long‐term analyses. (1st April 2019) - Costa, Nadège; Mounié, Michael; Bernard, Geraldine; Bieler, Laurent; Molinier, Laurent; Serrano, Elie; de Bonnecaze, Guillaume
Abstract : Objectives: Trans‐nasal endoscopic sphenopalatine artery ligation (TESPAL) and endovascular arterial embolisation both provide excellent success rates for intractable epistaxis. Recent economic models suggest that TESPAL could be a cost‐saving strategy. Our main aim was to perform cost‐effectiveness analyses on TESPAL compared with embolisation to treat patients with epistaxis. Design: We performed retrospective, monocentric, comparative analyses on patients referred to our centre and treated with embolisation or TESPAL. Setting: This economic evaluation was carried out from a payer's perspective (ie French National Health Insurance) within a time horizon of 12 months. Participants: Thirty‐seven TESPAL procedures and thirty‐nine embolisation procedures to treat intractable epistaxis were used in the analyses. Main outcome measures: The primary outcome is presented as the cost per 1% of non‐recurrence. Effectiveness was defined as avoiding recurrence of epistaxis during the 1‐year follow‐up. Cost estimates were performed from the payer's perspective. Results: Hospitalisation costs were higher for embolisation compared with TESPAL (5972 vs 3769 euros). On average, hospitalisation costs decreased by 41% when a patient was treated by TESPAL compared with an embolisation strategy ( P = 0.06). The presence of comorbidities increased hospitalisation costs by 79% ( P = 0.04). TESPAL enabled 1867€ to be gained in intractable epistaxis. Conclusions: The outcomes from our decision model confirm that TESPAL is more cost‐effective for patients with intractable epistaxis.